A saliva como amostra alternativa na avaliação da adesão ao tratamento hipoglicemiante de pacientes com Diabetes Mellitus tipo 2 no SUS - Baltazar, Heloisa De Faria [UNIFESP] (2020)
Type 2 Diabetes Mellitus (DM2) is characterized by a disorder of carbohydrate metabolism resulting from defects in insulin secretion and / or insulin action. The progression of this disease may lead to secondary events characterized by retinopathy, renal dysfunction, neuropathy, atherosclerosis and others. The diagnosis is made by demonstrating the hyperglycemic condition when fasting, which involves plasma glucose determination and the follow-up of a hypoglycemic treatment is made through the evaluation of glycated hemoglobin concentration. Monitoring of the diabetic patient's glycemic condition is of extreme importance to evaluate the adherence to the hypoglycemic pharmacotherapy. For this reason, it is convenient to use simple and fast analytical methods besides collecting non-invasive and painless biological samples. Recently, the use of saliva as an alternative biological sample is the focus of several studies, in which it is intended to replace the conventional usage of venous blood collection procedure. The goal of this study is to verify the usage of saliva sample as an alternative compared to venous blood (serum or plasma), in the evaluation of adherence to hypoglycemic treatment of patients suffering from DM2 and treated at the Sistema Único de Saúde – SUS (Single Healthcare System) in São Bernardo do Campo, Brazil. In this experiment, 68 patients (64 ± 12 years old) suffering from DM2 were selected, who were submitted to both venous blood and saliva collection, in addition to answering a standardized questionnaire on adherence to hypoglycemic treatment. The laboratory tests conducted on saliva and blood (serum or plasma) measured: blood glucose, urea, creatinine, uric acid, total cholesterol, HDL-cholesterol, LDL-cholesterol, VLDL-cholesterol and glycated hemoglobin. It concluded that 82% of patients adhered to hypoglycemic treatment based on glycated hemoglobin concentration (cutoff point 7.0%). Comparing the groups that adhered to the hypoglycemic treatment and those that did not, statistical differences were noticed (P<0.05) in the glucose, HDL-cholesterol, triglycerides parameters and insulin usage therapy. Glucose (plasma) and urea (serum) concentrations showed positive correlations when compared to saliva samples. Regarding the questionnaire, it was found that 35% of patients had “Positive Belief Barrier Tracking” and 83% had a “Positive Barrier of Memory Score”, while the “Positive Tracking” correlated with glycated hemoglobin. In summary, this study shows that it is possible to adopt saliva as an alternate sample to the laboratory evaluation to the adherence of DM2 patient to a hypoglycemic treatment. Studies with a larger number of patients will be necessary to validate the results presented here.